How cartoon characters and claims influence children's attitude towards a snack vegetable – An explorative cross-cultural comparison between Indonesia and Denmark. (January 2021) - Hémar-Nicolas, Valerie; Putri Hapsari, Hanum; Angka, Stephanie; Olsen, Annemarie
Highlights: A cross-cultural study about Danish and Indonesian children's responses to snack vegetable packaging. Positive effect of cartoon character on Danish children's evaluation of snack vegetable packaging. Greatest effect of cartoon character on Danes' packaging evaluation when congruent with vegetable. No effects of tasty or healthy claims on children's responses to snack vegetable. Methodological challenges involved in cross-cultural studies in children. Abstract: While the use of cartoon characters is recurrently blamed for encouraging unhealthy food habits in children, these techniques conversely appear to be highly relevant to promote healthy foods, specifically fruits and vegetables. In this context, our cross-cultural research project aims to explore to what extent a cartoon character associated with health- or taste-related claims on a snack vegetable influences 8- to 11-year-old children's evaluation of cucumber packaging and their willingness to consume this snack. The experiment is conducted with 162 Indonesian and 101 Danish children. Its design is 3 within-groups for the character (congruent character versus incongruent character versus no character) × 3 between-groups for the claim (healthy versus tasty versus no claim) × 2 between-groups for the country (Denmark versus Indonesia). The results show that an on-package character increases Danish children's packaging evaluation and that this effect is stronger when the character is perceptually congruent with cucumber (colour and shape). In contrast, no character has a direct effect on their willingness to eat cucumber, to request it from their parents, and to recommend it to a friend. Additionally, neither taste nor health claims influence children's packaging evaluation and intention. Regarding Indonesian children, their responses to packages are often more favourable than Danish children, but do not vary according to the character-claim combinations, except when they were asked to express their preference through a forced choice task. These cultural differences highlight the methodological challenges involved in cross-cultural studies.